Niepełnosprawność w systemach religijnych Japonii (Przegląd Religioznawczy – The Religious Studies Review, 2021)
The aim of this article is to present disability in Japan's Religious Systems. Attention will be paid to Sintoism, Buddhism, Confucianism, Christianity and folk religions. Depending on religion disability is treaten either as punishment or privilege and has a huge impact on those affected with disability and their families.